Comparative study of postoperative analgesia by epidural ketamine and ketamine plus dexamethasone in lower limb orthopedic surgery - Babita Agarwal; Pratik Jain (International Journal of Medical Research and Review, 2019)
Aim & Objectives: To compared the effect of ketamine and combination of ketamine plus dexamethasone on the duration of postoperative analgesia and to evaluate the effect of dexamethasone on postepidural backache and other complications.Methods: 50 patients (ASA I and II) posted for elective surgery of lower limb in orthopedics, were divided at random into two groups of 25 each. Patients in group I received Inj. Ketamine HCl 0.3 mg/kg diluted in 10 ml normal saline while patients in group II received ketamine HCl 0.3 mg/kg and dexamethasone 8 mg diluted in 10 ml normal saline postoperatively through epidural catheter. The relief of pain and perioperative sequelae were compared.Results: Groups were compared with respect to quality of epiduralanaesthesia and pain relief as felt by the patient. The quality of epidural anaesthesia was found adequate in 80% cases of group 2 and 76% cases of group 1. Pain relief was 20% excellent and 76% good in group 2 and 12% excellent and 68% good in group 1. In group I the mean duration of pain relief after epidural injection of ketamine 0.3 mg/kg was 363.91±180.94 min and in group II after epidural injection of ketamine 0.3 mg/kg with dexamethasone 8 mg was 582.63±182.03 min. These values differ markedly and are statistically highly significant (p<0.001).Conclusion: Ketaminecan be used epidurally safely for rapid onset and is effective for prolonged postoperative analgesia with minimum side effects and high acceptability. The duration can be further prolonged with the addition of dexamethasone and the incidence of postepidural backache is also minimised with dexamethasone.